History and the Concepts Underlying the Lebanese Maronite Order Affordable Housing Projects - Charbel Abboud; Houwayda Matta; Maroun Khater (Mediterranean Journal of Social Sciences, 2023)
Affordable housing is a worldwide crisis in the urban areas. In Lebanon, due to this crisis especially at the end of the Civil War, the Church took the initiative to implement affordable housing. Accordingly, the Lebanese Maronite Order (LMO) implemented affordable housing projects during its 300th Jubilee. The aim of this paper is to discuss the history and the concepts underlying the LMO affordable housing projects which was the subject of an evaluative research conducted in 2019 to evaluate the effectiveness of LMO’s projects. This assessment study combined the evaluation of the findings with the evaluation of the implementation. A questionnaire was given to the project's beneficiaries, and semi-structured interviews were conducted with the project's managers. This study confirms the consistency of this initiative with the mission of the LMO in accordance with the guidelines of the Catholic Church and the Human Right to Adequate Housing. Due to the current housing, political, social, and economical crisis in Lebanon, LMO and the ecclesiastical institutions must multiply these projects and the Lebanese government must apply the Right to Adequate Housing and must take the initiative to implement affordable housing in collaboration with the private sector and the non-for-profit organisations. Received: 5 April 2023 / Accepted: 29 June 2023 / Published: 5 July 2023